Yellowing-resistant water-based paint as well as preparation method and application thereof
By distributing nano cerium oxide in the nanosilicon dioxide framework in aqueous polyurethane coating and modifying organic amines, combined with asymmetric biquaternary ammonium salt surface activation, the problem of yellowing of aqueous polyurethane coating in the sunlight environment is solved, significantly improving the Its yellowing resistance and ultraviolet resistance are achieved.
Patent Information
- Application Number
- CN202411474413.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Water-based polyurethane coatings are prone to yellowing in sunlight environments, especially aromatic polyurethanes, and the prior art is difficult to effectively solve this problem.
By distributing nano cerium oxide as the core in the nanosilicon dioxide bone frame, and doping Si(OH)4 and Ce(OH)4 as the precipitant, organic amine modification is carried out to improve the Anti-UV properties; at the same time, asymmetric biquaternary ammonium salt surface activation is used to improve its dispersion performance in polyurethane emulsion.
It significantly improves the yellowing resistance of water-based polyurethane coatings, enhances its resistance to ultraviolet rays, and extends the duration of uny yellowing.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based coatings, and in particular relates to a yellowing-resistant water-based coating, a preparation method and application thereof. Background Art
[0002] Waterborne polyurethane is a new type of environmentally friendly polymer material with a wide range of adjustable soft and hard segments, good low temperature resistance, flexibility, wear resistance and mechanical properties. It can be prepared into coatings, leather, foam materials, etc., and has a very wide range of uses. However, when used as a coating, waterborne polyurethane often turns yellow. The reason can be attributed to the oxidation and yellowing of the film due to ultraviolet light exposure in the sunlight environment. Especially for aromatic polyurethane, the yellowing phenomenon is more serious. Therefore, it is necessary to consider improving its yellowing resistance from aspects such as raw materials and modification. Summary of the invention
[0003] The purpose of the present invention is to provide a yellowing-resistant water-based coating, a preparation method and application thereof, which are used to improve the yellowing-resistant performance of water-based polyurethane coatings.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a yellowing-resistant water-based coating comprises the following steps:
[0006] The polyurethane emulsion, defoamer and film-forming agent are mixed and stirred evenly, and the yellowing-resistant filler and pigment are added and mixed, and ultrasonic dispersion is performed evenly to obtain the yellowing-resistant water-based coating;
[0007] The preparation method of the yellowing-resistant filler comprises the following steps:
[0008] S1, take the vermiculite ore, heat it, cool it, immerse it in a 6 mol / L hydrochloric acid solution, heat it to 80°C and immerse it for 2-3 hours, filter it, take the solid phase, wash it, and dry it to obtain material A;
[0009] S2, taking the material A, anhydrous ethanol and tetraethylenediamine, mixing, stirring for 4-6 hours, and vacuum drying at 50° C. for 5-6 hours to obtain material B;
[0010] S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 10-15 min, keep stirring at a constant temperature of 70-80 ° C for 30-40 min, add cerium chloride solution, stir for 1-2 h, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5 L / min for 30-40 min, filter the solid phase, place it in deionized water, stir for 10-20 min, adjust the pH to 5.5-6.5, let it stand for 30-40 min, filter the solid phase, wash it, dry it, roast it at 250-350 ° C for 1.2-1.5 h, cool it, grind it, and sieve it to obtain material C;
[0011] S4, take acetonitrile and toluene, mix them, add 1-bromodocosane, stir for 20-30 min, add tetramethyl-hexanediamine, reflux at 75-85°C with stirring for 6-8 h, add 1-bromohexane, reflux at 75-85°C with stirring for 6-8 h, cool in an ice-water bath for 4-5 h, add ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 10-12 h to obtain material D;
[0012] S5. Mix the material C, material D and deionized water, stir at 60° C. for 3-4 hours, centrifuge, wash and dry the solid phase to obtain the yellowing-resistant filler.
[0013] As a preferred technical solution of the present invention, in step S1, the heat preservation treatment refers to heat preservation at 900° C. for 5 minutes.
[0014] As a preferred technical solution of the present invention, in step S2, the mass ratio of the material A, anhydrous ethanol and tetraethylenediamine is 8-12:50-60:1-2.
[0015] As a preferred technical solution of the present invention, in step S3, the dosage ratio of material B, sodium metasilicate nonahydrate, deionized water added for the first time, cerium chloride solution, and deionized water added for the second time is 6-8g: 2.38-3.42g: 200mL: 14.3-16.2mL: 50-60mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3.
[0016] As a preferred technical solution of the present invention, in step S4, the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and diethyl ether is 40-50:90-100:39-40:17.3-18.2:16.5-17.5:70-80.
[0017] As a preferred technical solution of the present invention, in step S5, the mass ratio of material C, material D, and deionized water is 1.2-1.5:0.08-0.12:60-80.
[0018] As a preferred technical solution of the present invention, the preparation method of the polyurethane emulsion comprises the following steps:
[0019] In a nitrogen atmosphere, polytetrahydrofuran and isophorone diisocyanate are mixed, stirred at 85° C. for 2-3 hours, cooled to 45° C., 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, and acetone are added, the temperature is raised to 80° C., stirred for 5-7 hours, cooled to 35° C., triethylamine is added, stirred for 20-30 minutes, deionized water is added for emulsification for 30-40 minutes, and acetone is removed by vacuum rotary evaporation to obtain the polyurethane emulsion.
[0020] As a preferred technical solution of the present invention, the mass ratio of polytetrahydrofuran, isophorone diisocyanate, 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, acetone, triethylamine, and deionized water is 16-18: 6-8: 0.4-0.5: 0.3-0.4: 0.8-1.2: 0.02-0.04: 30-40: 0.5-0.7: 50-55.
[0021] The yellowing-resistant water-based paint is prepared by the above-mentioned preparation method.
[0022] The application of the yellowing-resistant water-based paint refers to applying the yellowing-resistant water-based paint to the surface of wood, leather, and plastic.
[0023] Beneficial effects of the present invention:
[0024] The yellowing-resistant water-based coating disclosed in the present invention, as well as its preparation method and application, uses nano-cerium oxide as a core and distributes it in a nano-silicon dioxide skeleton frame, thereby preventing the agglomeration of nano-cerium oxide from weakening its anti-ultraviolet performance.
[0025] Furthermore, by introducing carbon dioxide as a precipitant, Si(OH)4 and Ce(OH)4 are co-precipitated by doping. In order to improve the co-precipitation of Si(OH)4 and Ce(OH)4 to form a uniformly dispersed system, the vermiculite is modified with organic amine to improve its adsorption effect on carbon dioxide, so that nano-silicon dioxide-cerium oxide is uniformly loaded in the vermiculite layer structure, thereby improving the anti-ultraviolet performance;
[0026] Furthermore, by using asymmetric diquaternary ammonium salt to surface activate the nano-silica-cerium oxide-loaded vermiculite, its dispersion performance in the polyurethane emulsion is improved, thereby improving the anti-ultraviolet performance of the polyurethane emulsion and improving its yellowing resistance. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0028] Example 1
[0029] A method for preparing a yellowing-resistant water-based coating comprises the following steps:
[0030] Take the polyurethane emulsion, defoamer and film-forming agent, mix and stir for 1 hour, add the yellowing-resistant filler and pigment, mix, and ultrasonically disperse for 25 minutes to obtain the yellowing-resistant water-based coating;
[0031] The mass ratio of the polyurethane emulsion, defoamer, film former, yellowing-resistant filler and pigment is 250:15:12:28:18;
[0032] The defoamer is an organosilicon defoamer purchased from Jinan Longcheng Organosilicon Co., Ltd.
[0033] The film-forming agent is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0034] The pigment is red iron oxide, purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0035] The preparation method of the polyurethane emulsion comprises the following steps:
[0036] In a nitrogen atmosphere, polytetrahydrofuran and isophorone diisocyanate were mixed, stirred at 85° C. for 2 h, cooled to 45° C., 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, and acetone were added, the temperature was raised to 80° C., stirred for 5 h, cooled to 35° C., triethylamine was added, stirred for 20 min, deionized water was added for emulsification for 30 min, and acetone was removed by vacuum rotary evaporation to obtain the polyurethane emulsion;
[0037] The mass ratio of the polytetrahydrofuran, isophorone diisocyanate, 2,2-dimethylolpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, acetone, triethylamine, and deionized water is 16:6:0.4:0.3:0.8:0.02:30:0.5:50;
[0038] The polytetrahydrofuran is poly(tetrahydrofuran), AVERAGE MN-2000, purchased from Guangzhou Nalong Chemical Co., Ltd.
[0039] The preparation method of the yellowing-resistant filler comprises the following steps:
[0040] S1, take vermiculite ore (purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.) and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 2h, filter it, wash the solid phase, and dry it to obtain material A;
[0041] S2, taking the material A, anhydrous ethanol, and tetraethylenediamine, mixing, stirring for 4 hours, and vacuum drying at 50° C. for 5 hours to obtain material B; the mass ratio of the material A, anhydrous ethanol, and tetraethylenediamine is 8:50:1;
[0042] S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 10 minutes, keep stirring at a constant temperature of 70°C for 30 minutes, add cerium chloride solution, stir for 1 hour, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5L / min for 30 minutes, filter out the solid phase and place it in deionized water, stir for 10 minutes, adjust the pH to 5.5, let it stand for 30 minutes, filter out the solid phase, wash it, dry it, roast it at 250°C for 1.2 hours, cool it, grind it, and pass it through a 250-mesh sieve to obtain material C; the dosage ratio of the material B, sodium metasilicate nonahydrate, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 6g:2.38g:200mL:14.3mL:50mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;
[0043] S4, take acetonitrile and toluene, mix, add 1-bromodocosane, stir for 20 minutes, add tetramethyl-hexanediamine, reflux and stir at 75°C for 6 hours, add 1-bromohexane, reflux and stir at 75°C for 6 hours, cool in an ice water bath for 4 hours, add ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 10 hours, and obtain material D; the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and ether is 40:90:39:17.3:16.5:70;
[0044] S5. Mix the material C, material D and deionized water, stir at 60° C. for 3 h, centrifuge, wash the solid phase, and dry to obtain the yellowing-resistant filler; the mass ratio of the material C, material D and deionized water is 1.2:0.08:60.
[0045] Example 2
[0046] A method for preparing a yellowing-resistant water-based coating comprises the following steps:
[0047] Take the polyurethane emulsion, defoamer and film-forming agent, mix and stir for 1.5 hours, add the yellowing-resistant filler and pigment, mix, and ultrasonically disperse for 30 minutes to obtain the yellowing-resistant water-based coating;
[0048] The mass ratio of the polyurethane emulsion, defoamer, film former, yellowing-resistant filler and pigment is 300:20:14:30:20;
[0049] The defoamer is an organosilicon defoamer purchased from Jinan Longcheng Organosilicon Co., Ltd.
[0050] The film-forming agent is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0051] The pigment is red iron oxide, purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0052] The preparation method of the polyurethane emulsion comprises the following steps:
[0053] In a nitrogen atmosphere, polytetrahydrofuran and isophorone diisocyanate were mixed, stirred at 85° C. for 2.5 h, cooled to 45° C., 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, and acetone were added, the temperature was raised to 80° C., stirred for 6 h, cooled to 35° C., triethylamine was added, stirred for 25 min, deionized water was added for emulsification for 35 min, and acetone was removed by vacuum rotary evaporation to obtain the polyurethane emulsion;
[0054] The mass ratio of the polytetrahydrofuran, isophorone diisocyanate, 2,2-dimethylolpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, acetone, triethylamine, and deionized water is 17:7:0.45:0.35:1.0:0.03:35:0.6:52;
[0055] The polytetrahydrofuran is poly(tetrahydrofuran), AVERAGE MN-2000, purchased from Guangzhou Nalong Chemical Co., Ltd.
[0056] The preparation method of the yellowing-resistant filler comprises the following steps:
[0057] S1, take vermiculite ore (purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.) and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 2.5h, filter it, wash the solid phase, and dry it to obtain material A;
[0058] S2, taking the material A, anhydrous ethanol, and tetraethylenediamine, mixing, stirring for 5 hours, and vacuum drying at 50° C. for 5.5 hours to obtain material B; the mass ratio of the material A, anhydrous ethanol, and tetraethylenediamine is 10:55:1.5;
[0059] S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 12 minutes, keep stirring at a constant temperature of 75°C for 35 minutes, add cerium chloride solution, stir for 1.5 hours, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5L / min for 35 minutes, filter out the solid phase, place it in deionized water, stir for 15 minutes, adjust the pH to 6.0, let it stand for 35 minutes, filter out the solid phase, wash it, dry it, roast it at 300°C for 1.35 hours, cool it, grind it, and pass it through a 250-mesh sieve to obtain material C; the dosage ratio of the material B, sodium metasilicate nonahydrate, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 7g:2.81g:200mL:15.4mL:55mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;
[0060] S4, take acetonitrile and toluene, mix, add 1-bromodocosane, stir for 25 minutes, add tetramethyl-hexanediamine, reflux and stir at 80°C for 7 hours, add 1-bromohexane, reflux and stir at 80°C for 7 hours, cool in an ice water bath for 4.5 hours, add diethyl ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 11 hours, and obtain material D; the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and diethyl ether is 45:95:39.5:17.8:17.1:75;
[0061] S5. Mix the material C, material D and deionized water, stir at 60° C. for 3.5 hours, centrifuge, wash the solid phase and dry to obtain the yellowing-resistant filler; the mass ratio of the material C, material D and deionized water is 1.35:0.10:70.
[0062] Example 3
[0063] A method for preparing a yellowing-resistant water-based coating comprises the following steps:
[0064] Take the polyurethane emulsion, defoamer and film-forming agent, mix and stir for 2 hours, add the yellowing-resistant filler and pigment, mix, and ultrasonically disperse for 35 minutes to obtain the yellowing-resistant water-based coating;
[0065] The mass ratio of the polyurethane emulsion, defoamer, film former, yellowing-resistant filler and pigment is 350:25:16:32:22;
[0066] The defoamer is an organosilicon defoamer purchased from Jinan Longcheng Organosilicon Co., Ltd.
[0067] The film-forming agent is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0068] The pigment is red iron oxide, purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0069] The preparation method of the polyurethane emulsion comprises the following steps:
[0070] In a nitrogen atmosphere, polytetrahydrofuran and isophorone diisocyanate were mixed, stirred at 85° C. for 3 h, cooled to 45° C., 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, and acetone were added, the temperature was raised to 80° C., stirred for 7 h, cooled to 35° C., triethylamine was added, stirred for 30 min, deionized water was added for emulsification for 40 min, and acetone was removed by vacuum rotary evaporation to obtain the polyurethane emulsion;
[0071] The mass ratio of the polytetrahydrofuran, isophorone diisocyanate, 2,2-dimethylolpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, acetone, triethylamine, and deionized water is 18:8:0.5:0.4:1.2:0.04:40:0.7:55;
[0072] The polytetrahydrofuran is poly(tetrahydrofuran), AVERAGE MN-2000, purchased from Guangzhou Nalong Chemical Co., Ltd.
[0073] The preparation method of the yellowing-resistant filler comprises the following steps:
[0074] S1, take vermiculite ore (purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.) and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 3h, filter it, wash the solid phase, and dry it to obtain material A;
[0075] S2, taking the material A, anhydrous ethanol, and tetraethylenediamine, mixing, stirring for 6 hours, and vacuum drying at 50° C. for 6 hours to obtain material B; the mass ratio of the material A, anhydrous ethanol, and tetraethylenediamine is 12:60:2;
[0076] S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 15 minutes, keep stirring at a constant temperature of 80°C for 40 minutes, add cerium chloride solution, stir for 2 hours, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5L / min for 40 minutes, filter out the solid phase and place it in deionized water, stir for 20 minutes, adjust the pH to 6.5, let it stand for 40 minutes, filter out the solid phase, wash it, dry it, roast it at 350°C for 1.5 hours, cool it, grind it, and pass it through a 250-mesh sieve to obtain material C; the dosage ratio of the material B, sodium metasilicate nonahydrate, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 8g:3.42g:200mL:16.2mL:60mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;
[0077] S4, take acetonitrile and toluene, mix, add 1-bromodocosane, stir for 30 minutes, add tetramethyl-hexanediamine, reflux and stir at 85°C for 8 hours, add 1-bromohexane, reflux and stir at 85°C for 8 hours, cool in an ice-water bath for 5 hours, add diethyl ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 12 hours, and obtain material D; the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and diethyl ether is 50:100:40:18.2:17.5:80;
[0078] S5. Mix the material C, material D and deionized water, stir at 60° C. for 4 h, centrifuge, wash the solid phase and dry to obtain the yellowing-resistant filler; the mass ratio of the material C, material D and deionized water is 1.5:0.12:80.
[0079] Comparative Example 1
[0080] The difference from Example 2 is that the preparation method of the yellowing-resistant filler comprises the following steps:
[0081] S1. Take the vermiculite ore and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 2.5h, filter it, wash the solid phase, and dry it to obtain material A;
[0082] S2, take the material A, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 12 minutes, keep stirring at a constant temperature of 75°C for 35 minutes, add cerium chloride solution, stir for 1.5 hours, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5L / min for 35 minutes, filter out the solid phase, place it in deionized water, stir for 15 minutes, adjust the pH to 6.0, let it stand for 35 minutes, filter out the solid phase, wash it, dry it, roast it at 300°C for 1.35 hours, cool it, grind it, and pass it through a 250-mesh sieve to obtain material C; the dosage ratio of the material A, sodium metasilicate nonahydrate, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 7g:2.81g:200mL:15.4mL:55mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;
[0083] S3, take acetonitrile and toluene, mix, add 1-bromodocosane, stir for 25 minutes, add tetramethyl-hexanediamine, reflux and stir at 80°C for 7 hours, add 1-bromohexane, reflux and stir at 80°C for 7 hours, cool in an ice water bath for 4.5 hours, add ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 11 hours, and obtain material D; the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and ether is 45:95:39.5:17.8:17.1:75;
[0084] S4. Mix the material C, material D and deionized water, stir at 60° C. for 3.5 hours, centrifuge, wash the solid phase and dry to obtain the yellowing-resistant filler; the mass ratio of the material C, material D and deionized water is 1.35:0.10:70.
[0085] Comparative Example 2
[0086] The difference from Example 2 is that the preparation method of the yellowing-resistant filler comprises the following steps:
[0087] S1. Take the vermiculite ore and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 2.5h, filter it, wash the solid phase, and dry it to obtain material A;
[0088] S2, taking the material A, anhydrous ethanol, and tetraethylenediamine, mixing, stirring for 5 hours, and vacuum drying at 50° C. for 5.5 hours to obtain material B; the mass ratio of the material A, anhydrous ethanol, and tetraethylenediamine is 10:55:1.5;
[0089] S3, take the material B, deionized water, mix, ultrasonic stirring for 12 minutes, keep stirring at 75 ° C for 35 minutes, add cerium chloride solution, stir for 1.5 hours, pass carbon dioxide-nitrogen mixed gas with a flow rate of 0.5L / min for 35 minutes, filter out the solid phase and place it in deionized water, stir for 15 minutes, adjust the pH to 6.0, let it stand for 35 minutes, filter out the solid phase, wash, dry, roast at 300 ° C for 1.35 hours, cool, grind, and pass through a 250-mesh sieve to obtain material C; the dosage ratio of the material B, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 7g:200mL:15.4mL:55mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;
[0090] S4, take acetonitrile and toluene, mix, add 1-bromodocosane, stir for 25 minutes, add tetramethyl-hexanediamine, reflux and stir at 80°C for 7 hours, add 1-bromohexane, reflux and stir at 80°C for 7 hours, cool in an ice water bath for 4.5 hours, add diethyl ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 11 hours, and obtain material D; the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and diethyl ether is 45:95:39.5:17.8:17.1:75;
[0091] S5. Mix the material C, material D and deionized water, stir at 60° C. for 3.5 hours, centrifuge, wash the solid phase and dry to obtain the yellowing-resistant filler; the mass ratio of the material C, material D and deionized water is 1.35:0.10:70.
[0092] Comparative Example 3
[0093] The difference from Example 2 is that the preparation method of the yellowing-resistant filler comprises the following steps:
[0094] S1. Take the vermiculite ore and keep it at 900℃ for 5min, cool it, immerse it in 6mol / L hydrochloric acid solution, heat it to 80℃ and immerse it for 2.5h, filter it, wash the solid phase, and dry it to obtain material A;
[0095] S2, taking the material A, anhydrous ethanol, and tetraethylenediamine, mixing, stirring for 5 hours, and vacuum drying at 50° C. for 5.5 hours to obtain material B; the mass ratio of the material A, anhydrous ethanol, and tetraethylenediamine is 10:55:1.5;
[0096] S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 12 minutes, keep stirring at a constant temperature of 75°C for 35 minutes, add cerium chloride solution, stir for 1.5 hours, pass a carbon dioxide-nitrogen mixed gas with a flow rate of 0.5L / min for 35 minutes, filter out the solid phase and place it in deionized water, stir for 15 minutes, adjust the pH to 6.0, let it stand for 35 minutes, filter out the solid phase, wash it, dry it, roast it at 300°C for 1.35 hours, cool it, grind it, and pass it through a 250-mesh sieve to obtain the yellowing-resistant filler; the dosage ratio of the material B, sodium metasilicate nonahydrate, the deionized water added for the first time, the cerium chloride solution, and the deionized water added for the second time is 7g:2.81g:200mL:15.4mL:55mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3.
[0097] Comparative Example 4
[0098] The difference from Example 2 is that the temperature of constant temperature stirring in the preparation step S3 of the yellowing-resistant filler is 65°C.
[0099] Comparative Example 5
[0100] The difference from Example 2 is that the temperature of constant temperature stirring in the preparation step S3 of the yellowing-resistant filler is 55°C.
[0101] Comparative Example 6
[0102] The difference from Example 2 is that the temperature of constant temperature stirring in the preparation step S3 of the yellowing-resistant filler is 85°C.
[0103] Comparative Example 7
[0104] The difference from Example 2 is that the temperature of constant temperature stirring in the preparation step S3 of the yellowing-resistant filler is 95°C.
[0105] Comparative Example 8
[0106] The difference from Example 2 is that the temperature of constant temperature stirring in the preparation step S3 of the yellowing-resistant filler is room temperature.
[0107] Performance Testing
[0108] The water-based coatings prepared in Examples 1-3 and Comparative Examples 1-8 were sprayed and cured to perform a yellowing resistance test. The test results are shown in Table 1 below.
[0109] Table 1
[0110] Yellowing index change value Yellowing resistance time Example 1 8 112h Example 2 6 116h Example 3 9 111h Comparative Example 1 24 98h Comparative Example 2 29 87h Comparative Example 3 26 93h Comparative Example 4 13 106h Comparative Example 5 15 102h Comparative Example 6 14 104h Comparative Example 7 22 99h Comparative Example 8 25 95h
[0111] As shown in Table 1, the waterborne polyurethane coatings prepared in Examples 1-3 of the present application have good yellowing resistance. The present application uses nano-cerium oxide as the core and distributes it in the nano-silicon dioxide skeleton to avoid the agglomeration of nano-cerium oxide and the weakening of the anti-ultraviolet performance.
[0112] Furthermore, by introducing carbon dioxide as a precipitant, Si(OH)4 and Ce(OH)4 are co-precipitated by doping. In order to improve the co-precipitation of Si(OH)4 and Ce(OH)4 to form a uniformly dispersed system, the vermiculite is modified with organic amine to improve its adsorption effect on carbon dioxide, so that nano-silicon dioxide-cerium oxide is uniformly loaded in the vermiculite layer structure, thereby improving the anti-ultraviolet performance;
[0113] Furthermore, by using asymmetric diquaternary ammonium salt to surface activate the nano-silica-cerium oxide-loaded vermiculite, its dispersion performance in the polyurethane emulsion is improved, thereby improving the anti-ultraviolet performance of the polyurethane emulsion and improving its yellowing resistance.
[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a yellowing-resistant water-based coating, characterized in that: The following steps are involved: The polyurethane emulsion, defoamer and film-forming agent are mixed and stirred evenly, and the yellowing-resistant filler and pigment are added and mixed, and ultrasonic dispersion is performed evenly to obtain the yellowing-resistant water-based coating; The preparation method of the yellowing-resistant filler comprises the following steps: S1. Take the vermiculite ore, treat it by heat preservation, cool it, immerse it in a 6 mol / L hydrochloric acid solution, heat it to 80°C and immerse it for 2-3 hours, filter it, wash the solid phase, and dry it to obtain material A; S2, taking the material A, anhydrous ethanol and tetraethylenediamine, mixing, stirring for 4-6 hours, and vacuum drying at 50° C. for 5-6 hours to obtain material B; S3, take the material B, sodium metasilicate nonahydrate, and deionized water, mix them, ultrasonically stir for 10-15 min, keep stirring at a constant temperature of 70-80 ° C for 30-40 min, add cerium chloride solution, stir for 1-2 h, pass carbon dioxide-nitrogen mixed gas at a flow rate of 0.5 L / min for 30-40 min, filter the solid phase, place it in deionized water, stir for 10-20 min, adjust the pH to 5.5-6.5, let it stand for 30-40 min, filter the solid phase, wash it, dry it, roast it at 250-350 ° C for 1.2-1.5 h, cool it, grind it, and sieve it to obtain material C; S4, take acetonitrile and toluene, mix them, add 1-bromodocosane, stir for 20-30 min, add tetramethyl-hexanediamine, reflux at 75-85°C with stirring for 6-8 h, add 1-bromohexane, reflux at 75-85°C with stirring for 6-8 h, cool in an ice-water bath for 4-5 h, add ether, shake and stir to wash, filter and take the solid phase, vacuum dry at 50°C for 10-12 h to obtain material D; S5. Mix the material C, material D and deionized water, stir at 60° C. for 3-4 hours, centrifuge, wash and dry the solid phase to obtain the yellowing-resistant filler.
2. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: In step S1, the heat preservation treatment refers to heat preservation at 900°C for 5 minutes.
3. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: In step S2, the mass ratio of material A, anhydrous ethanol and tetraethylenediamine is 8-12:50-60:1-2.
4. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: In step S3, the dosage ratio of material B, sodium metasilicate nonahydrate, deionized water added for the first time, cerium chloride solution, and deionized water added for the second time is 6-8g: 2.38-3.42g: 200mL: 14.3-16.2mL: 50-60mL; the concentration of the cerium chloride solution is 0.3mol / L; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:
3.
5. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: In step S4, the mass ratio of acetonitrile, toluene, 1-bromodocosane, tetramethyl-hexanediamine, 1-bromohexane and diethyl ether is 40-50:90-100:39-40:17.3-18.2:16.5-17.5:70-80.
6. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: In step S5, the mass ratio of material C, material D, and deionized water is 1.2-1.5:0.08-0.12:60-80.
7. The method for preparing a yellowing-resistant water-based coating according to claim 1, characterized in that: The preparation method of the polyurethane emulsion comprises the following steps: In a nitrogen atmosphere, polytetrahydrofuran and isophorone diisocyanate are mixed, stirred at 85° C. for 2-3 hours, cooled to 45° C., 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, and acetone are added, the temperature is raised to 80° C., stirred for 5-7 hours, cooled to 35° C., triethylamine is added, stirred for 20-30 minutes, deionized water is added for emulsification for 30-40 minutes, and acetone is removed by vacuum rotary evaporation to obtain the polyurethane emulsion.
8. The method for preparing a yellowing-resistant water-based coating according to claim 7, characterized in that: The mass ratio of the polytetrahydrofuran, isophorone diisocyanate, 2,2-dihydroxymethylpropionic acid, trimethylolpropane, 1,4-butanediol, dibutyltin dilaurate, acetone, triethylamine and deionized water is 16-18: 6-8: 0.4-0.5: 0.3-0.4: 0.8-1.2: 0.02-0.04: 30-40: 0.5-0.7: 50-55.
9. A yellowing-resistant water-based coating prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the yellowing-resistant water-based paint according to claim 9, characterized in that: The application refers to applying the yellowing-resistant water-based paint to the surface of wood, leather and plastic.
